Integrated Science Learning Webbed Type in Permaculture Theme and BRADeR Model to Enhance Science Literacy Competence of Junior High School Students - Syaifullah Syaifullah; Fida Rachmadiarti; Beni Setiawan; Edi Suwandi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research aims to assess the scientific literacy of State Junior High School 1 Ngoro students in integrated science learning using the webbed type with a permaculture theme and the BRADeR model. Method: This descriptive quantitative study involves 80 students from State Junior High School 1 Ngoro: 16 from class IX-A (limited trial) and 64 from IX-B and IX-C (broader trial). Data collection was conducted using a science literacy competence test instrument consisting of 10 essay questions designed according to three dimensions of scientific literacy proficiency. The validity assessment by three experts showed that 9 out of 10 questions scored an average of 4, categorizing them as